Pengaruh Belanja Daerah, Dana Desa, Investasi Dalam Negeri, UMR, dan Kemiskinan Terhadap PDRB Tahun 2018-2021 - Evita Wafa Enggarosa; Nur Sabrina Nadatul Ain; Abdul Ilah Najih; Brenda Aprilla Zul’ardiva; Siti Sintya Hidayatulloh; Bintis Ti’anatud Diniati (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This study aims to analyze the factors influencing Gross Regional Domestic Product (GRDP) in Indonesia, namely regional spending, village funds, investment, Regional Minimum Wage (UMR), and poverty levels. The analysis used is panel data using the fixed effects approach (FEM) and random effects (REM) in the period 2018–2023. The study shows that UMR and regional spending have a significant effect on GRDP, while village funds, investment, and poverty are not significant. These findings imply that optimization of regional spending allocation and testing of village fund and investment policies must be developed to support economic development. This study provides theoretical and practical contributions for policy makers in designing more effective and sustainable regional economic development strategies